Agri-Food System Innovation Workshop Report - CSIRO; CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2017)
This workshop report is a summary record of the second workshop (https://cas.cgiar.org/isdc/events/workshop-agri-food-system-innovation-reframing-conversation) convened by the ISPC/CSIRO Agri-food systems innovation and partnership initiative, and held from 27 to 29 June at ICRISAT in Hyderabad, India. The report attempts to capture, in brief, the deliberations of the participants, including key outcomes and follow-up actions to further the initiative’s campaign and ongoing dialogue on the reframing of the common narrative on agri-food System Innovation.